Karakteristik Dan Manajemen Pasien Dengan Fistula Perianal Di RSU Cut Meutia Kabupaten Aceh Utara Tahun 2018 - 2021 - Muhammad Sayuti; Sofia Rizka; Moh Arief Kresna (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Perianal fistula is a condition where a cavity forms in the area around the rectum and fills with pus. Perianal fistula is an anorectal disorder that arises due to obstruction of the anal crypts. If left untreated perianal fistula can lead to serious complications such as perineal gangrene and sepsis. A large number of perianal abscesses will recur within a year or two, especially if predisposing factors are present. This study aims to determine patient characteristics and management of perianal fistula patients at Cut Meutia General Hospital in 2018-2021. This is a retrospective descriptive study using secondary data from perianal fistula patients at Cut Meutia General Hospital. The results of the study were 11 patients diagnosed with perianal fistula based on medical record data that met the inclusion and exclusion criteria. Based on the age range criteria, the most patients with perianal fistulas were in the age group range of 20 - 40 and 41-60 years, each of which was 5 patients (45.45%), male patients were the most, namely 9 patients (81.18%), based on the operation of perianal fistula patients who underwent surgery the most using LIFT procedures were 7 patients (63.63%), and based on the history of recurrence, the most patients who experienced new/primary cases of perianal fistula were as many as 9 patients (81.8%).